2014
DOI: 10.1002/ps.3890
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of furanocoumarins from parsley againstMeloidogynespp.

Abstract: Parsley exhibits promising nematicidal activity as an organic amendment and as a source of nematotoxic furanocoumarins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…As a promising alternative to chemical nematicides, research on the botanical nematicide is receiving increasing attention . The current study found that crude extract of W. indica roots has strong nematocidal activity against J2 of M. incognita.…”
Section: Discussionmentioning
confidence: 70%
“…As a promising alternative to chemical nematicides, research on the botanical nematicide is receiving increasing attention . The current study found that crude extract of W. indica roots has strong nematocidal activity against J2 of M. incognita.…”
Section: Discussionmentioning
confidence: 70%
“…[ 35 ] The levels of psoralen, methoxsalen, oxypeucedanin, and bergapten from the methanolic extract of P. crispum aerial parts were measured before and they were 1.77–46.04 mg/kg of plant weight. [ 36 ] Pimpinella anisum oil was active against Gram-positive bacteria ( B. cereus and S. aureus ) with MIC of 62.5–125 μg/mL while its MIC against Gram-negative bacteria ( E. coli , Klebsiella pneumoniae and P. aeruginosa ) was >500 μg/mL and its methanolic extract showed MIC of 500 μg/mL against S. aureus . [ 37 ] The methanolic extract had MIC of 5000 μg/mL against S. aureus , E. coli , and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coumarin's use as the lead compound for the preparation of potent pharmacological molecules, it has also received considerable research attention for its interesting insecticidal, nematicidal, allelopathic, and antimicrobial activities in agriculture. [8][9][10][11][12][13] From the literature, we found that the antifungal activity of coumarins was certainly related to the nonpolar substituent at its 8-position. 14) These findings have made coumarins a very attractive lead for further transformations at the 8-position with nonpolar substituents.…”
Section: Introductionmentioning
confidence: 99%